PENGUKURAN PENCAHAYAAN VIDEOTRON DI KAWASAN BUNDARAN HOTEL INDONESIA DKI JAKARTA - Endah Setyaningsih; Ida Zureidar; Yohanes Calvinus; Luthfi Arifandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
Videotron is a medium that shows videos, which are currently widely used as advertising media. Videotron is installed on the side of the road, especially on protocol roads to attract motorists and pedestrians to view advertisements. Videotron installation using support poles or affixed to existing buildings. On the one hand, videotron is currently a very reliable advertising medium for advertisers, because it makes it easier for consumers to see advertising products, along the road while driving or walking. Besides being used as an advertising medium, videotron is also widely used by local governments as a medium of information for the public to fulfill one of the public services. But on the other hand, the light effect of the videotron if it is excessive and also the sudden change in light, greatly affects motorized vehicle users and pedestrians. The existence of this glare effect needs special attention, for that the PKM team partnered with the Indonesian Illuminating Engineering Society (HTII), to measure videotron lighting. HTII is a professional association engaged in lighting, which also pays attention to videotron lighting, especially the glare effects caused by videotron lighting, which if excessive will interfere with the visual comfort and safety of road users, especially motorized vehicle users. Measurements were carried out along Thamrin road, especially in the Indonesian hotel roundabout area. The purpose of the measurement is not only to determine the luminance value of the videotron, it can also be an input for the DKI Jakarta Regional Government and other regional governments as the videotron management party, in making rules for videotron. The results of this PKM implementation are in the form of videotron measurement data, namely the luminance and illuminance values, which are displayed in the form of tables or graphs, making it easier for further analysis to be carried out.ABSTRAK:Videotron merupakan media yang menayangkan video, yang saat ini banyak digunakan sebagai media iklan. Videotron terpasang di berbagai sisi jalan, terutama di jalan protokol untuk menarik minat bagi pengendara kendaraan bermotor dan pejalan kaki. Pemasangan videotron menggunakan tiang penyangga atau ditempelkan pada bangunan yang sudah ada. Satu sisi videotron saat ini merupakan media iklan yang sangat diandalkan bagi pengiklan, karena memudahkan konsumen untuk melihat produk iklan, di sepanjang jalan saat berkendara atau berjalan kaki. Selain digunakan sebagai media iklan, videotron juga banyak digunakan oleh pemerintah daerah sebagai media informasi bagi masyarakat untuk memenuhi salah satu pelayanan publik. Namun disisi lain efek cahaya dari videotron jika berlebihan dan juga perubahan cahaya secara tiba-tiba, sangat mempengaruhi pengguna kendaraan bermotor dan pejalan kaki. Adanya efek silau ini perlu menjadi perhatian khusus, untuk itu tim PKM bermitra dengan Himpunan Teknik Iluminasi Indonesia (HTII), untuk melakukan pengukuran pencahayaan videotron. HTII merupakan sebuah asosiasi profesi yang bergerak dibidang pencahayaan, yang juga memberikan perhatian pada pencahayaan videotron, terutama efek silau yang ditimbulkan dari pencahayaan videotron, yang jika berlebihan akan mengganggu kenyamanan visual dan keselamatan pengguna jalan raya terutama pengguna kendaraan bermotor. Pengukuran dilakukan di sepanjang jalan Thamrin, khususnya di kawasan bundaran hotel Indonesia. Tujuan pengukuran selain untuk mengetahui nilai luminansi cahaya videotron, juga bisa menjadi masukan bagi Pemda DKI Jakarta dan Pemda lainnya sebagai pihak pengelola videotron, dalam pembuatan aturan untuk videotron. Hasil dari pelaksanaan PKM ini berupa data hasil pengukuran videotron, yaitu nilai luminansi dan iluminansi, yang ditampilkan dalam bentuk tabel atau grafik, sehingga memudahkan untuk dilakukan analisis selanjutnya